Insulator-on-Conductor Fouling Amplifies Aqueous Electrolysis Rates - Rodriguez, H.M.; Martyniuk, M.; Iyer, K.S.; Ciampi, Simone (2024)
The chemical industry is a major consumer of fossil fuels. Several chemical reactions of practical value proceed with the gain or loss of electrons, opening a path to integrate renewable electricity into chemical manufacturing. However, most organic molecules have low aqueous solubility, causing green and cheap electricity-driven reactions to suffer from intrinsically low reaction rates in industry’s solvent of choice: water. Here, we show that a strategic, partial electrode fouling with hydrophobic insulators (oils and plastics) offsets kinetic limitations caused by poor reactant solubility, opening a new path for the direct integration of renewable electricity into the production of commodity chemicals. Through electrochemiluminescence microscopy, we reveal for the oxidation of organic reactants up to 6-fold reaction rate increase at the “fouled” oil-electrolyte-electrode interface relative to clean electrolyte-electrode areas. Analogously, electrodes partially masked (fouled) with plastic patterns, deposited either photolithographically (photoresists) or manually (inexpensive household glues and sealants), outperform clean electrodes. The effect is not limited to reactants of limited water solubility, and, for example, net gold electrodeposition rates are up to 22% larger at fouled than clean electrodes. In a system involving a surface-active reactant, rate augmentation is driven by the synergy between insulator-confined reactant enrichment and insulator-induced current crowding, whereas only the latter and possibly localized decrease in iR drop near the insulator are relevant in a system composed of non-surface-active species. Our counterintuitive electrode design enhances electrolysis rates despite the diminished area of intimate electrolyte-electrode contact and introduces a new path for upscaling aqueous electrochemical processes.